APLIKASI ECO-ENZYME DAN BIOCHAR TERHADAP PERTUMBUHAN DAN HASIL TANAMAN BAWANG MERAH (Allium cepa L. var. aggregatum) - Zuliati, Septiarini; Sitepu, Cindy Cahyani Br; Ismadi; Nasution, Wahyu Isnanda; Humaira, Mira; Ramadhani, Almuna; Handayani, Turi (Agrotekma: Jurnal Agroteknologi dan Ilmu Pertanian, 2025)
The increase in shallot production is not followed by an increase in productivity. In this regard, productivity needs to be increased through fertilization using eco enzyme organic fertilizer and biochar which contain many important nutrients for soil fertility. This research used a Randomized Block Design (RBD) arranged factorially and had three replications. The first factor was the addition of Eco enzyme consisting of 3 levels, namely E0 = without addition of eco-enzyme, E1 = addition of 10 ml/l eco-enzyme, and E2 = addition of 20 ml/l eco-enzyme. The second factor was the concentration of biochar with 3 doses, namely B0 = without addition of biochar, B1 = addition of 15 tons/ha biochar, and B2 = addition of 20 tons/ha biochar. Some of the variables observed were plant height, number of leaves, diameter of tubers per cluster, number of tubers per cluster, wet weight of tubers, and dry weight of tubers. The results showed that the application of eco-enzyme affected the growth parameters of plant height and number of leaves as well as the results of dry weight of tubers per clump. The application of biochar affected the observation parameters of tuber diameter per clump, number of tubers, wet weight of tubers, and dry weight of tubers. The combination of eco-enzyme and rice husk biochar treatments has not shown a significant interaction effect on the growth and yield of shallots.Keywords: Shallots, Eco-enzyme, Biochar, Rice husk